2018
DOI: 10.1111/cns.12809
|View full text |Cite
|
Sign up to set email alerts
|

LINGO‐1 antibody ameliorates myelin impairment and spatial memory deficits in the early stage of 5XFAD mice

Abstract: Our results demonstrated that myelin injury was an early event in 5XFAD mice even prior to emergence of deposition of Aβ. Intervention with the LINGO-1 antibody could attenuate impaired spatial memory deficits by remyelination, which suggested that myelin injury was involved in spatial memory deficits and remyelination may be a potential therapeutic strategy in early stage of AD or mild cognitive impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 39 publications
(65 reference statements)
5
45
0
Order By: Relevance
“…Richard et al, reported in this last line of 5xFAD spatial memory de cits were only visible after 7 months of age (73). Others reported spatial memory impairment at an earlier age when using the water maze but with a very small difference between WT and 5xFAD (74,75).. In the present study, none of the groups tested in the SYM test performed above chance level indicating lack of recognition in all groups examined.…”
Section: Discussionsupporting
confidence: 45%
“…Richard et al, reported in this last line of 5xFAD spatial memory de cits were only visible after 7 months of age (73). Others reported spatial memory impairment at an earlier age when using the water maze but with a very small difference between WT and 5xFAD (74,75).. In the present study, none of the groups tested in the SYM test performed above chance level indicating lack of recognition in all groups examined.…”
Section: Discussionsupporting
confidence: 45%
“…We found a statistically significant CAW treatment-dependent increase in these synaptic markers in the cortex, while there was a significant increase in synaptophysin in the hippocampus and an increasing trend in Psd95 (p=0.026) with CAW treatment. An interesting observation in the progression of 5XFAD pathology is that spine loss (4-9 months) [62] occurs subsequent to cognitive dysfunction (3-6 months) [35,[63][64][65][66] and Aβ plaque formation (two months) [67]. This is different from the progression in Tg2576, which manifests synaptic damage at an early stage of pathological development (4.5 months) [68,69] with a corresponding decrease in synaptic density markers [70] prior to Aβ plaque development (10 months) [71] and cognitive deficiencies (one year) [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the current studies, the 6-month-old 5xFAD mice displayed impairment of social recognition memory but not spatial memory. While memory impairment in this 5xFAD mouse strain has been detected as young as 1 month of age through the Morris water maze [493], [494], others have found that 5xFAD mice display normal spatial memory function in this test until 7 months of age [238] or even up to 12 months of age [495]. Likewise, recognition memory has been shown to emerge at 4 months of age [495] in one study and at 9 months of age in another [468].…”
Section: Discussionmentioning
confidence: 94%